Strengthening Women Farmer Groups through Integrated Empowerment Strategies: The Case of Kalisidi Village, Indonesia - Fajrin Pramana Putra; Albertus Fajar Irawan; Muhammad Iqbal Fauzan (Publication of the International Journal and Academic Research, 2026)
Kalisidi Village, located in Ungaran Barat District, Semarang Regency, possesses significant agricultural potential supported by fertile land and favorable climatic conditions. The majority of its population works in the agricultural sector, including active participation from local Women's Farmer Groups (Kelompok Wanita Tani/KWT). Building on previous community service programs that introduced innovations such as automated irrigation systems and organic fertilizer production, this study explores the feasibility and strategic development of a Fruit Seedling Center managed by local KWT. Despite having strong motivation and available basic infrastructure, the KWTs face three core challenges: limited knowledge of propagation techniques (e.g., grafting), lack of access to simple agricultural technology, and weak digital literacy for marketing their products. These constraints hinder the optimal production and distribution of high-quality fruit seedlings. This analysis proposes an integrated empowerment program involving interdisciplinary collaboration from agriculture, engineering, business, and communication fields. The program includes technical training, provision of propagation tools and greenhouse construction, as well as digital marketing workshops. The goal is to establish a sustainable and community-managed seedling center that improves local economic resilience and serves as a model of inclusive, tech-enabled rural agribusiness development.